Formulación de un plan estratégico para la empresa Motores del Valle MOTOVALLE SAS (2020-2024) - Ferrer Guzmán, Diego (Universidad Antonio Nariño, 2021)
This work aims to create a strategic plan to the company Motovalle SAS for the years 2020-2024, its nature is descriptive and the topics are addressed with methodological aspects related to the main theme and the automotive sector from its beginnings in the country, the theoretic component comprises two major nods from planning and strategic thinking with basic elements to contextualize and justify the importance of planning in the projection of companies over time and the exercise of their economic activities in a conscious and sustainable way, the proposal is develop in six stages whereby addresses a strategic planning tools such as the description of the organization, the analysis of the environments, the definition of the competitive profile, the DOFA matrix, the formulation of strategic imperatives and the formulation of an action plan, the research process allowed to analyze multiple sources of information primary and secondary that allow to obtain an overall picture of the Colombian automotive sector and identify the profile of the contemporary costumer, as well as new market trends in terms of comfort, innovation and technology, aspects that will be seen broadly and transversally since those are vital elements for the success and competitiveness of organizations in the sector.